Impact of Nonpharmaceutical Interventions on ICU Admissions During Lockdown for Coronavirus Disease 2019 in New Zealand-A Retrospective Cohort Study - Gonzenbach, Tobias P; McGuinness, Shay P; Parke, Rachael L; Merz, Tobias M (Critical care medicine, 2021)
Nonpharmaceutical interventions are implemented internationally to mitigate the spread of severe acute respiratory syndrome coronavirus 2 with the aim to reduce coronavirus disease 2019-related deaths and to protect the health system, particularly intensive care facilities from being overwhelmed. The aim of this study is to describe the impact of nonpharmaceutical interventions on ICU admissions of non-coronavirus disease 2019-related patients. Retrospective cohort study. Analysis of all reported adult patient admissions to New Zealand ICUs during Level 3 and Level 4 lockdown restrictions from March 23, to May 13, 2020, in comparison with equivalent periods from 5 previous years (2015-2019). Twelve-thousand one-hundred ninety-two ICU admissions during the time periods of interest were identified. Patient data were obtained from the Australian and New Zealand Intensive Care Society Adult Patient Database, Australian and New Zealand Intensive Care Society critical care resources registry, and Statistics New Zealand. Study variables included patient baseline characteristics and ICU resource use. Nonpharmaceutical interventions in New Zealand were associated with a 39.1% decrease in ICU admission rates (p < 0.0001). Both elective (-44.2%) and acute (-36.5%) ICU admissions were significantly reduced when compared with the average of the previous 5 years (both p < 0.0001). ICU occupancy decreased from a mean of 64.3% (2015-2019) to 39.8% in 2020. Case mix, ICU resource use per patient, and ICU and hospital mortality remained unchanged. The institution of nonpharmaceutical interventions was associated with a significant decrease in elective and acute ICU admissions and ICU resource use. These findings may help hospitals and health authorities planning for surge capacities and elective surgery management in future pandemics.